Contamination of Aflatoxins Induces Severe Hepatotoxicity Through Multiple Mechanisms - Hua, Zhenglai; Liu, Rui; Chen, Youwen; Liu, Guangzhi; Li, Chenxi; Song, Yurong; Cao, Zhiwen; Li, Wen; Li, Weifeng; Lu, Cheng; Liu, Yuanyan (Frontiers in pharmacology, 2021)
Aflatoxins (AFs) are commonly contaminating mycotoxins in foods and medicinal materials. Since they were first discovered to cause “turkey X” disease in the United Kingdom in the early 1960s, the extreme toxicity of AFs in the human liver received serious attention. The liver is the major target organ where AFs are metabolized and converted into extremely toxic forms to engender hepatotoxicity. AFs influence mitochondrial respiratory function and destroy normal mitochondrial structure. AFs initiate damage to mitochondria and subsequent oxidative stress. AFs block cellular survival pathways, such as autophagy that eliminates impaired cellular structures and the antioxidant system that copes with oxidative stress, which may underlie their high toxicities. AFs induce cell death via intrinsic and extrinsic apoptosis pathways and influence the cell cycle and growth via microribonucleic acids (miRNAs). Furthermore, AFs induce the hepatic local inflammatory microenvironment to exacerbate hepatotoxicity via upregulation of NF-κB signaling pathway and inflammasome assembly in the presence of Kupffer cells (liver innate immunocytes). This review addresses the mechanisms of AFs-induced hepatotoxicity from various aspects and provides background knowledge to better understand AFs-related hepatoxic diseases.